Identifikasi Kandungan Komponen Babi pada Daging Curah dan Produk Olahan Daging Menggunakan Metode ELISA Sandwich di Balai Besar Veteriner Wates - Meilinia, Shafina Meilinia; Achmad, Agung Budianto; Diyantoro, Diyantoro; Chrismanto, Dony (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
Background: Indonesians have relatively high dietary requirements. Meat and processed items are frequently counterfeited in today's world. Pork is a low-cost protein provider that is cheap and readily available. As a result, some traders began substituting the whole meat and processed products with pork. In protecting the community, BBVet Wates conducted ELISA Sandwich testing. Purpose: To find out the addition of pork content in meat and processed products and the effectiveness of ELISA for species tests. Method: ELISA type sandwich. Result: In 2019, there were 45 positive samples and 113 negative samples, while in 2020, there were 23 positive samples and 59 negative samples. Conclusion: In 2020, there will be a decrease in cases of pork addition by 0.45% from 2019. The Elisa method species test has high accuracy and sensitivity. Keywords: Species Test; ELISA; Meat and Processed Products.